Biological variation in serum thyroid, iron metabolism, and plasma bone metabolism biomarkers in patients with type 2 diabetes mellitus - Wang, Xia; Zhang, Mei; Liu, Zhi; Li, Chuan; Li, Yujue; Huang, Hengjian; He, He; Yu, Xijie (Frontiers in Endocrinology, 2025)
ObjectivesVariability in biomarkers is crucial for clinical decision-making in individuals with type 2 diabetes mellitus (T2DM). The biological variation (BV) of biomarkers associated with thyroid function, iron metabolism, and bone metabolism may show population-specific differences. This study aims to evaluate the biological variation of sixteen biomarkers in T2DM patients and compare these with variations observed in a healthy population.MethodsTwenty-four T2DM patients, aged 43 to 67 and in stable condition, were enrolled. Blood samples were collected biweekly for three months. Analysis of variance models were used to assess the BV, including within-subject BV (CVI), between-subject BV (CVG), analytical variation, reference change value (RCV), index of individuality (II), the number of samples required for steady-state set points (NHSP), and analytical performance specifications for all biomarkers.ResultsFemales exhibited lower CVI estimates for thyroid-stimulating hormone, parathyroid hormone, and phosphate compared to males. No significant differences in CVI estimates were observed between T2DM patients and healthy individuals across the study. However, the CVG estimates for cortisol and iron were significantly lower in T2DM patients compared to the healthy individuals.ConclusionsBV data is critical for the precise interpretation of serial biomarker level changes in T2DM patients. It is deemed reasonable to use RCVs for four bone metabolism markers and five thyroid biomarkers, derived from a healthy population, as a reference for monitoring T2DM patients.